MODEL INTERNALISASI NILAI SYUKUR MELALUI VALUE CLARIFICATION TECHNIQUE PADA PEMBELAJARAN KIMIA UNTUK MENGUATKAN KARAKTER RELIGIUS:Kuasi Eksperimen di SMA Teuku Nyak Arif Fatih, Banda Aceh - Sri Risky Ananda, - (2023)
The background of this research is motivated by the massive of moral degradation that occurs among adolescents. Technological developments make teenagers have a capitalist-minded, material oriented, opportunistic and consumptive. Moral deviations do not only occur in a large context, but also in small context such as basic ethics. At this time, the habit of asking help, apologize and thank you has disappreared, which indicates a lack of gratitude among adolescents. The problem in this research is how to internalize the value of gratitude through VCT in chemistry learning to strengthen religious character. The purpose of this study is to develop a model of internalizing the value of gratitude through VCT in chemistry learning to strengthen religious character at SMA Teuku Nyak Arif Fatih Bilingual School. This research is a mixed method with an exploratory approach. Data collection techniques used were tests, questionnaires, observations and interviews. Qualitative data were analyzed by reducing and presenting data and drawing conclusions. While the analysis of quantitative data using N-Gain and Mann Whitney tests. The results showed that the internalization of the value gratitude through VCT was carried out by combining the PBL model and VCT approach. In the implementation, it can be seen that the activity of students fluctuated in the experimental class. The combination of the PBL and VCT models requires more time because the teacher ensures that the cognitive and affective aspects of students are achieved simultaneously. This combination has advantages because students can find value and get new views regarding chemical material which can be a medium in instilling the value of gratitude. While the challenge is to provide the right portion in conveying cognitive and affective aspects so that learning time can be carried out in accordance with the duration of class hours. Keywords: Internalization, Gratitude, PBL, VCT, Chemistry Learning